Attitudes and factors associated with adverse patient outcomes as perceived by nurses and medical doctors - Ivana Vukotić; Mile Despotović; Bojan Joksimović; Dejan Bokonjić; Biljana Mijović; Milena Božinović; Radmila Balaban; Maja Abazović; Kristina Drašković; Marija Milić (Биомедицинска истраживања, 2022)
Introduction: . The patient and his safety should be at the center of quality health care, which is a challenge for every health system. Ad verse patient outcomes (APO) are defined as damage caused by a drug or other intervention in a primary, secondary or tertiary health care fa cility, which results in a complication of the primary or the emergence of a new disease or injury. The aim of our study was to determine how frequent the APO are, and to determine the differences between nurs es and doctors in the frequency, causes and attitudes towards APO. Methods: . This cross-sectional study included 100 health professionals, nurses and medical doctors employed at the primary and secondary level of health care. The research was conducted in the period from May to October 2020. The questionnaire was partially taken from a general questionnaire offered on the website of the Agency for Health care Research and Quality and the standardized Perceived stress scale was used to measure the degree of subjective stress. Results: . Forty-four health professionals (44%) experienced adverse patient outcomes in their career, doctors (52%) significantly more often than nurses (36%) (p = 0.039). More than a half of respondents (52.3%) declared that APO happens few times a month. Seventy per cent of the respondents blame their own stress burden as the main factor associated with APO. Doctors more often than nurses (69.2%) blame problems in communication between health professionals as the main cause of APO (27.8%) (p = 0.046). Conclusion: . For doctors, the main cause of APO is problem in commu nication, while nurses more often think that patient safety is priority when compared to doctors. Almost two thirds of respondents blame their own stress burden as a factor associated with APO.
Keywords: frequency; attitudes; adverse patient outcomes